Critical Care Nephrology and Renal Replacement Therapy in Children (Springer International Publishing, 2018)
This book represents an invaluable resource for professionals for the diagnosis and treatment of acute kidney injury (AKI) in children and how to select and deliver the appropriate form of renal replacement therapy (RRT). Experts from all over the globe have come together to share their wide experience in the field of Critical Care Nephrology in children. Paediatric critical care nephrology is a complex and highly specialised field, presenting challenges and management strategies that are often quite distinct from those seen in adult practice. Therefore, it is high time to address all the topics in the field of critical care nephrology in children in a unique book which is the first of its kind. This book covers the basics as well as advances in the field of Critical Care Nephrology. Each chapter is dedicated to practical aspects of a particular topic elucidating various management decision points. Each chapter is also accompanied with algorithms, figures and protocols in tabulated format. Information on how to manage specific conditions are contextualized with relevant background anatomy, physiology and biochemistry and practical examples. At the end of the chapter, there are key learning points. Paediatricians, nephrologists and paediatric intensivists, as well as paediatric critical care and nephrology nurses in all countries will find this book an invaluable reference text.